HAND GESTURE AND DETEKSI WAJAHDETECTION USING RASPBERRY PI - Helfy Susilawati; Ade Rukmana; Fitri Nuraeni (Informatika, Universitas Jenderal Soedirman, 2023)
Face detection is currently used for various purposes, one of which is to record employees attendance. This strategy is ineffective since the employees still can hack the attendance by making their own photos and put them in their desks. If they are unable to come to the office,they can always ask their colleagues to submit their already available photos.Therefore, an alternative that can complement the current face detection method is highly needed.One of the methods that can be used is hand gesture detection.This study aims to detect hand gestures made by the employees to ensure whether they really come to work or not,so the chance for manipulation is quite small.For the purpose of hand gesture recognition, this study utilized Local Binary Pattern Histogram algorithm. LBPH is an algorithm used for the image matching process between images that have been given training and images taken in real time.The hand gesture image was first taken using a raspberry pi camera and then processed to examine whether it matches the registered ID or not.The results showed that ID recognition by using hand gestures is detectable and is in accordance with the registered ID.The number recognition in hand gestures includes numbers 1 to 10. The test results showed that, the average time required for reading hand gestures using a laptop was 9.2 seconds, while that of using raspberry was 14,2 seconds.Motion reading using a raspberry takes longer than that of using a laptop because the laptop's performance is higher than that of a raspberry.